Differences in morphology and motor abilities in 12 years tennis players - Sedar, M.; Marinovic, M. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The development of the game of tennis and permanent growth of its level encourages undertaking the training already in early childhood. Players from almost all tennis federation take part in international competitions already at 12 years of age. At that time young athletes have already spent five to six years in clubs usually exercising boys and girls together. The purpose of the research was to analyse similarities and differences in morphological characteristics and motor abilities of young tennis players of different gender. Methods Study group was composed of 19 boys and 16 girls (age 10.95 ± 1.02 and 11.03 ± 1. ±07 years respectively). To assess the body composition 30 morphological parameters were measured. According to them body mass index (BMI), sum of seven skinfolds and somatotype were calculated. Motor abilities were examined by seventeen tests. To compare boys and girls analysis of variance was performed. Results Height and weight for boys and girls were 154.48 ± 9.25 (mean ± standard deviation) and 150.35 ± 11.07 centimeters as well as 42.12 ± 7.06 and 39.53 ± 9.03 kilograms respectively. Among 30 morphological parameters statistically significant differences exist only in knee breadth presenting boys (9.21 ± 0.43 cm) with bigger knee breath than girls (8.70 ± 0.48 cm) (f = 8.69; p< 0.01). Comparing these two samples in set of seventeen motor abilities statistical significant differences were found only in flexibility presenting girls more flexible (6.34 ± 5.9 cm) than boys (-2.2 ± 9.2 cm) (f = 9.59; p< 0.00). In other motor abilities tests for speed, agility, strength and endurance differences were not found. Discussion/Conclusion This examination presents young boys and girls tennis players as similar samples in morphological characteristics and motor abilities, allow them to exercise together without different approach in training load.